Biodiesel generated from Jatropha (Jatropha curcas Linn.) seeds selected based on various genotypes crossbred. (December 2020) - Maftuchah,; Zainudin, Agus; Winaya, Aris; Rahmadesi, Yuyun
Abstract: The supply of fossil fuels is not parallel with resources availability. Hence, the development of alternatives fuels and bioenergy is significant to supply energy fulfill and environmentally friendly as well. Jatropha curcas Linn. seed was known as one of biodiesel source. In this study, we have selected several genotypes crossbred of J. curcas plant to get the crude oil and then converted to biodiesel fuels. The six crossbred genotypes of Jatropha, i.e., JC5, JC6, JC7, JC18, IP3A, and IP3P, were using as samples which planted on a dry land area of Pasuruan district, East Java, Indonesia. The planting trial was applied Randomized Completely Block Designed (RCBD). The result showed was not significantly different on 100 seeds dry weight, and the highest crude oil was found on JC7 by 47.58 %. Furthermore, there were no differences in free fatty acid content, acid value, and biodiesel yield, while the highest saponification value reached on JC6 with 230.01 mg KOH g −1 and JC18 with 228.61 mg KOH g −1 . The highest esterification value was obtained by JC6 (226.14 mg KOH g −1 ) and JC18 (224.32 mg KOH g −1 ). It concluded that the selected Jatropha genotypes potentially for biodiesel production.